2013
DOI: 10.1038/pr.2013.69
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of pattern of injury and quantitative MRI on days 1 and 3 in term newborns with hypoxic–ischemic encephalopathy

Abstract: Background: Brain injury in term neonatal hypoxicischemic encephalopathy (HIE) emerges on magnetic resonance imaging (MRI) by day 3. This study aimed to address the relationship of MRI, diffusion tensor imaging (DTI), and MR spectroscopic imaging (MRSI) findings on days 1 and 3 in a prospective cohort of term newborns with HIE. Methods: A total of 24 term newborns with HIE were prospectively studied with MRI on days 1 and 3; 19 were imaged with DTI and MRSI on days 1 and 3. MRI was assessed using validated sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
29
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 31 publications
1
29
0
1
Order By: Relevance
“…DWI is a valuable MRI sequence with the ability to accurately detect injury as early as 24–72 h of life, and when combined with T1-W, T2-W and DWI sequences in the first 2- to 5-day window provides an indication of timing of injury [19, 2931]. The Barkovich system initially used only T1-W and T2-W sequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DWI is a valuable MRI sequence with the ability to accurately detect injury as early as 24–72 h of life, and when combined with T1-W, T2-W and DWI sequences in the first 2- to 5-day window provides an indication of timing of injury [19, 2931]. The Barkovich system initially used only T1-W and T2-W sequences.…”
Section: Discussionmentioning
confidence: 99%
“…the Bayley-III at an optimal age of 18–24 months. Validation of our scoring system against an established neurodevelopmental assessment tool allows for earlier identification of the potential functional impairment and can provide physicians with the information to guide management, specifically developmental therapy through intervention programs [9, 29, 33]. …”
Section: Discussionmentioning
confidence: 99%
“…Serial neuroimaging has shown that brain injury evolves over days, if not weeks, which means that early conventional MRI is not the ideal modality for the prediction of encephalopathy in the critical first few hours after birth, because lesions do not become visible until 7-10 days of life. 10,18-20 Diffusion tensor imaging and magnetic resonance spectroscopic imaging may be able to identify brain lesions within the first 3 days of life, 21 but affected neonates are usually too sick to take out of the neonatal intensive care unit (NICU) at this time, and many are born in hospitals where even conventional MRI is not available.…”
mentioning
confidence: 99%
“…The imaging pattern of HIE has been classified into three types (4,23); parasagittal lesions, involving cortico-subcortical regions, profound lesions located in the basal ganglia or thalamus, and multi-cystic encephalomalacia. Parasagittal lesions are typically associated with milder HIE (24).…”
Section: Discussionmentioning
confidence: 99%